Construction of Novel Plasmids for Eradicating Dengue Disease Using Recombinant Yeast Microbiota - Hossain, Sk Amir; Sheikh Shahjada Sangit; Rima Akter (Journal of Science and Technology, 2024)
With several dengue vaccines available that vary in effectiveness, paratransgenesis could provide an additional method for managing and possibly eradicating the dengue disease. The research in this work has focused on production of anti-dengue Dicer2/DCR2 and R2D2 proteins in yeast which are responsible for viral RNA degradation through siRNA pathway. In line of this work, pPICZ A_Pir1_Dcr2 and pPICZ A_Pir1_R2D2 novel plasmids are designed that would enable expression and genetic immobilization of our target proteins in the cell surface of yeast. The genetic cassette of the constructed plasmids contains AOX1 promoter, PIR1 gene and 6xHis genetic tag. The drosophila melanogaster (fruit fly) genes Dcr2 and R2D2 are then inserted into the designed genetic cassette of pPICZ A_Pir1_Dcr2 and pPICZ A_Pir1_R2D2 plasmids for construction of pPICZ A_Pir1_Dcr2 and pPICZ A_Pir1_R2D2 final plasmids. Both of the final plasmids are designed in such a way that would enable precise control of gene expression of our target enzymes in yeast and could be transformed with Pichia caribbica, Pichia ohmeri and Pichia guilliermondii. The transformed yeasts can then be introduced into mosquitoes Aedes aegypti either directly using a baited trap or encapsulated/seeded/oviposited recombinant yeasts into water to contaminate aquatic juvenile forms of mosquitoes.